2022
DOI: 10.3390/ijms23084120
|View full text |Cite
|
Sign up to set email alerts
|

KRAS: A Druggable Target in Colon Cancer Patients

Abstract: Mutations in KRAS are among the most frequent aberrations in cancer, including colon cancer. KRAS direct targeting is daunting due to KRAS protein resistance to small molecule inhibition. Moreover, its elevated affinity to cellular guanosine triphosphate (GTP) has made the design of specific drugs challenging. Indeed, KRAS was considered ‘undruggable’. KRASG12C is the most commonly mutated variant of KRAS in non-small cell lung cancer. Currently, the achievements obtained with covalent inhibitors of this varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 137 publications
0
6
0
Order By: Relevance
“…Furthermore, the role of lysosomal sequestration in drug accumulation, whether a potential mechanism for tumoral sensitization or cellular resistance that may be overwhelmed by very high dosing [29,30], requires further investigation. KRAS-mutant mCRC urgently needs more (targeted) therapeutic options; patients with these cancers do not respond to the otherwise clinically bene cial strategies blocking the pathway KRAS is involved in signalling [51][52][53]. Although recent work from Fukada et al has shown that harbouring a KRAS-G12V mutation causes osimertinib resistance in NSCLC [54], we show high drug activity in all three KRASmutant mCRC PDTOs.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, the role of lysosomal sequestration in drug accumulation, whether a potential mechanism for tumoral sensitization or cellular resistance that may be overwhelmed by very high dosing [29,30], requires further investigation. KRAS-mutant mCRC urgently needs more (targeted) therapeutic options; patients with these cancers do not respond to the otherwise clinically bene cial strategies blocking the pathway KRAS is involved in signalling [51][52][53]. Although recent work from Fukada et al has shown that harbouring a KRAS-G12V mutation causes osimertinib resistance in NSCLC [54], we show high drug activity in all three KRASmutant mCRC PDTOs.…”
Section: Discussionmentioning
confidence: 52%
“…Finally, in the multi‐omic analysis of different SCS subtypes, we were surprised to find that although the activation degree of KRAS pathway at the transcriptome level was significantly increased in SCS2 subtype compared with other subtypes, the somatic mutation of KRAS was significantly enriched in SCS4 subtype and the PCA score of subtype 1 goblet cell signature in the KRAS mutant group was also significantly higher compared with that in the KRAS wild‐type group. We hypothesized that this result may be due to the presence of other factors that inhibit KRAS signaling activation in the SCS4 subtype [ 36 ]. Therefore, the specific link between KRAS mutation and goblet cell accumulation and differentiation in colon cancer needs to be further examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The MSI tumor is often accompanied by high immunogenicity and high T-cell in ltration microenvironment [47,48], so immune checkpoint inhibitors (ICIs) are more effective in treating RCC than LCC and RC [49,50]. KRAS is involved in signaling pathways activated by EGFR [51], and mutations of KRAS can lead to tumor resistance to anti-EGFR antibodies [52].…”
Section: Discussionmentioning
confidence: 99%